2014
DOI: 10.5424/sjar/2014122-4096
|View full text |Cite
|
Sign up to set email alerts
|

Influence of feeding system on growth performance, carcass characteristics and meat and fat quality of Avileña-Negra Ibérica calves’ breed

Abstract: The effect of feeding system (calves reared under free-range conditions supplemented with concentrate vs. calves fed on concentrate and cereal straw in confinement) during finishing period on growth performance, carcass traits and meat and fat quality was investigated. Fourteen entire males of Avileña-Negra Ibérica breed were used. The feeding system had no effect on growth performance, carcass characteristics, muscle colour, drip losses and intramuscular fat (IMF) percentage in Longissimus thoracis. Free-rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…The omental fat was more saturated and less insaturated than IMF. As in the present study in Avileña-Negra Ibérica calves reared under freerange conditions supplemented with concentrate, Daza et al (2014) also observed that omental fat had higher Σ SFA and lower Σ PUFA proportions than IMF.…”
Section: Fat Qualitysupporting
confidence: 87%
“…The omental fat was more saturated and less insaturated than IMF. As in the present study in Avileña-Negra Ibérica calves reared under freerange conditions supplemented with concentrate, Daza et al (2014) also observed that omental fat had higher Σ SFA and lower Σ PUFA proportions than IMF.…”
Section: Fat Qualitysupporting
confidence: 87%
“…The fatty acid composition of the meat waste (Table 2) revealed the dominance of unsaturated fatty acids (53.36 ±0.33) over saturated fatty acids (46.64 ±0.19). Since the existing literature provides no data on the fatty acid content in butcher waste, a bibliographic review of the studies reporting the fatty acid content in different animal meats and fats was conducted [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. The review revealed that the fatty acid content varies greatly depending on whether the sample is flesh or lard and also on the origin of the sample (beef, lamb, rabbit, chicken, etc.).…”
Section: Characteristics Of the Meat Wastementioning
confidence: 99%